Aphid incidence and its correlation with different environmental factors - Hasan, MR; Ahmad, M; Rahman, MH; Haque, MA (Journal of the Bangladesh Agricultural University, 2010)
The aphid incidence and its correlation with environmental factors were studied. Mustard variety "Sampad" was used as test crop. Aphid incidence varied significantly at various parts of mustard plant and time of the day. The highest number of aphid was observed in the vegetative parts of the mustard plant in the morning. High cloudiness, relative humidity and dew point favoured the aphid population and slight rain fall quickly declined the aphid population. Among the different environmental factors maximum temperature, dew point and sun shine hours were positively correlated with aphid population and minimum temperature, relative humidity and wind speed were negatively correlated with aphid population. Keywords: Mustard aphid; Incidence; Environmental factors DOI: 10.3329/jbau.v7i1.4791 J. Bangladesh Agril. Univ. 7(1): 15-18, 2009